DIRECT THE LOOK FOR WOMEN'S HEALTH: TRENDS OF SCIENTIFIC RESEARCH ABOUT THE THEMATIC ABORTION (Fiep Bulletin - online, 2011)
Abortion is still a public health problem and is one of the most prominent themes in the discussions involving the health of women. This is a controversial subject that articulates various positions and personal conflicts, cultural, religious and social. This study aims to examine the contents of the thematic studies bristle abortion/miscarriage spontaneous. Deals is a type of study conducted by the systematic review literature on the theme of abortion / miscarriage, in the databases LILACS, MEDLINE, ADOLEC and BDENF. After applying the inclusion criteria, we obtained a sample of 14 study on the descriptor abortion, and 23 for the descriptor miscarriage, totaling well, 37 studies. Regarding that same year were published, it is emphasized in 2005 with 100% BDENF 53.86% in LILACS, ADOLEC at 50 and 40 in MEDLINE, the descriptor miscarriage, as compared to abortion, the year q was most prominent was 2009 with 50% in MEDLINE, 50% in BDENF, LILACS 25% and 50% at ADOLEC. Regarding the same regions that were found out to Midwest with 28.52% of the descriptor induced abortion, and 34.78% in relation to miscarriage. Among the publications found the theme spontaneous abortion was 43.43% from other approaches, without qualitative or quantitative, and on abortion is 50% with another type of methodological approach. Thus it is concluded that the subject in focus still needs to have, but scientific studies, thus enabling further discussion in scientific circles.
Keywords: Women; Abortion; Miscarriage